Screening Cardiovascular Risk in Patients with High Depression Scores - Yakar, Burkay; Ertekin, Yusuf Haydar (Professional Medical Publications, 2018)
Objective: Protection against cardiovascular diseases is provided by the dynamics of risk screening and counseling of primary health care services. Depression is known to pose a risk for cardiovascular diseases. The aim of our study was to determine which specific features of well-known depressed people who had not yet experienced a cardiovascular event were associated with cardiovascular risk. Methods: This study was conducted in patients at the Corum Gulabibey Family Health Center between June 2016 and June 2017. Patients without a known cardiovascular disease were subjected to Beck Depression Inventory (BDI) and Framingham risk scale. Framingham risk scores were compared by dividing the participants into two groups according to having Beck depression scores of equal/above 10 points (high BDI = HBDI) and below 10 points (low BDI = LBDI). Results: Age, LDL, total cholesterol, triglyceride, and blood pressure were all correlated with risk scores. In contrast, HDL and body mass index were only correlated with the risk scores in HBDI participants. From the HBDI patients, those who were obese had higher risk scores than those without obesity. Conclusion: Obesity is a high cardiovascular risk predictor that can be screened at one site in depression. While the body mass index of depressed individuals was correlated with the cardiovascular risk, this index being above 30 was indicative of high cardiovascular risk.
Keywords: Beck Depression Inventory; Cardiovascular Risk; Framingham Risk Score; Obesity; Primary Healthcare Services